Analisis Kualitas Pelayanan bagi Disabilitas dan Lanjut Usia di Dinas Kependudukan dan Catatan Sipil Kabupaten Banyuasin - Jauhari, M. Tantowi; Semil, Nurma; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
The purpose of this study is to analyze the Quality of Services for The Disabled and Elderly in the Population and Civil Registry Office of Banyuasin Regency. The results of the study revealed that the Quality of Services for The Disabled and Elderly in the Population and Civil Registry Office of Banyuasin Regency was good. This can be seen based on the Analysis of Service Quality for The Disabled and Elderly in the Population and Civil Registry Office of Banyuasin Regency which includes the dimensions and indicators used are: Tangibles / physical products ; Reliability ; Responsiveness ; Assurance ; Empathy all of which are of good quality. It is necessary to make efforts to further improve socialization to rural communities about the importance of population documents and the requirements for handling population documents, so that more and more people with disabilities and the elderly understand and understand the importance of having a population document, because now almost all institutions use population documents as a tool for approval; Optimization of facilities and infrastructure for the implementation of public services at the Banyuasin Regency Population and Civil Registry Office, such as optimizing the use of signs, as well as optimizing facilities and infrastructure for queuing; Increasing access to population administration services for all communities in Banyuasin Regency.